Acute Hepatitis Is a Prominent Presentation of the Multisystem Inflammatory Syndrome in Children: A Single‐Center Report. Issue 5 (27th October 2020) - Cantor, Amanda; Miller, Jonathan; Zachariah, Philip; DaSilva, Bernardo; Margolis, Kara; Martinez, Mercedes
Abstract : Background and Aims: A newly recognized multisystem inflammatory syndrome in children (MIS‐C) has had a paradigm‐shifting effect on the perception of severe acute respiratory syndrome, coronavirus‐2 (SARS‐CoV‐2) illness severity in children. We report the clinical and biochemical features of liver involvement, and the comorbidities that present with hepatitis, in a substantial cohort of patients. Approach and Results: This is a retrospective cohort study of 44 patients with MIS‐C admitted at Morgan Stanley Children's Hospital of New York‐Presbyterian during April and May 2020. We evaluated the number of patients who developed hepatitis and examined both demographics and inflammatory laboratory values to ascertain those that were at higher risk for liver involvement and more severe disease. Hepatitis was present in 19 subjects (43%) and was associated with more severe disease. Persons with hepatitis had significantly higher rates of shock at presentation (21.1% vs. 0%; P = 0.008), greater respiratory support requirement (42.1% vs. 12%; P = 0.005), and longer hospitalization times (median, 7 [interquartile range IQR, 5, 10] vs. 4 days [IQR, 3.5, 6.5]; P < 0.05). Patients with hepatitis also had significantly higher levels of ferritin (706.9 vs. 334.2 mg/mL; P < 0.01), interleukin‐6 (233.9 vs. 174.7 pg/mL; P < 0.05), troponin (83.0 vs. 28.5 ng/L; P < 0.05), and B‐type natriuretic peptide (7, 424.5 vs. 3, 209.5 pg/mL; P < 0.05). The single patient with liver failure also developed multiorgan failure requiring vasopressors, hemodialysis, and mechanical ventilation. All patients were discharged, though >50% had persistent hepatitis up to 1 month after discharge. Conclusions: Hepatitis is common in children with MIS‐C and is associated with a more severe presentation and persistent elevation of liver function tests in many. Despite the positive outcomes reported here, close follow‐up is warranted given the limited knowledge of the long‐term impact of SARS‐CoV‐2 on the liver.